(untitled) (KULT_online, 2012)
Hans Ulrich Gumbrecht argues in favour of a new approach to literary texts. By analysing Stimmungen (the German word refers to moods, atmospheres, climate, tunes and tunings) which are preserved by literary works, this approach makes it possible to access a specific Stimmung with regard to historical moments. Following a complex theoretical introduction, Gumbrecht demonstrates how these readings work and how readers can benefit from them by giving various examples, such as songs by Walther von der Vogelweide, Shakespeare’s sonnets, Thomas Mann’s Death in Venice, and even songs by Janis Joplin. Despite many stimulating ideas, the approach fails to be convincing; it is subjective, arbitrary and, finally, it appears to be shaped by a melancholy due to old age which dominates the overall Stimmung and influences Gumbrecht’s readings.